Characterization and functional analysis of novel circulating NK cell sub-populations. (12th March 2019) - Khummuang, Saichit; Chuensirikulchai, Kantinan; Pata, Supansa; Laopajon, Witida; Chruewkamlow, Nuttapol; Mahasongkram, Kodchakorn; Sugiura, Nobuo; Watanabe, Hideto; Tateno, Hiroaki; Kamuthachad, Ludthawun; Wongratanacheewin, Surasakdi; Takheaw, Nuchjira; et al.
Abstract: Natural killer (NK) cells are innate lymphoid cells having potent cytolytic function that provide host defense against microbial infections and tumors. Using our generated monoclonal antibody (mAb), named FE-1H10, new NK cell sub-populations in peripheral blood were identified. The molecules recognized by mAb FE-1H10 were expressed on a sub-population of CD3 − CD56 dim NK cells. The epitope recognized by mAb FE-1H10 was demonstrated to be N -glycan and proven to be different from CD57. Upon K562 stimulation, the CD56 dim FE-1H10 + NK cell sub-population exhibited significantly lower cytolytic function with low ability to degranulate and release cytolytic granules compared to the CD56 dim FE-1H10 − NK cell sub-population. Moreover, the CD56 dim FE-1H10 + NK cells produced less IFN-γ and TNF-α than the CD56 dim FE-1H10 − NK cells. We demonstrated here that mAb FE-1H10 could identify two sub-populations of circulating CD56 dim NK cells with different functions. Our discovery of new sub-populations of NK cells improves our understanding of NK cell biology and may lead to the development of new approaches for NK cell therapy. Abstract : An antibody that identifies sub-populations among CD56 dim NK cells